Pengelompokan Kata Berdasarkan Kemiripan Ucapan Pada Kamus Menggunakan Algoritma Metaphone Pada Sistem Operasi Android - Aditya Dwi Maryanto; Yuda Munarko; Yufis Azhar (Jurnal Repositor, 2019)
Indonesia is an archipelagic country consisting of various tribes and cultures and different languages. One of them is the Sumbawa language used by the people of the western part of the island of Sumbawa. Sumbawa language has 4 dialects namely Samawa, Taliwang, Jereweh, and Tongo. In Sumbawa there are also homophonic, homonim, and homograph words. Grouping words based on the similarity of speech to the Sumbawa dictionary used Metaphone algorithm on the android operating system is discussed in this study. Metaphone algorithms can be applied to multiple languages with rules that have been modified according to the desired language characteristic. Based on the results of testing the recall and precision on the new rules Metaphone algorithm can be concluded that the grouping of words based on similarity of speech in Sumbawa language can be said to be effective. The average percentage index of the recall test is 98,97% and the precision is 78,52%.